Peran Wanita Kristen Terhadap Misi Menurut Alkitab : Sebuah Tinjauan Teologis - Linda Joyce; Timotius Sukarna (Jurnal Filsafat dan Teologi Katolik, 2024)
The role of women in Christian missions is often overlooked, despite church history and the Bible recording their significant contributions to the spread of the gospel. Mission is a calling for all believers regardless of gender, as stated in the Great Commission (Matthew 28:19-20). This study aims to highlight the role of women in missions from a biblical perspective and its application in today's church. Using a qualitative method based on a literature review, this study analyses various biblical female figures involved in missionary work, such as Mary Magdalene, Lydia, Deborah, Esther, and Priscilla.The results of the study show that biblical women have a wide range of roles in various aspects of spiritual and social life, whether as leaders, prophets, teachers, or supporters of ministry. Women like Deborah and Esther show that women's leadership is not alien to God's plan, while figures like Mary Magdalene and Lydia prove that women also had key roles in the spread of the gospel. In the early church, names like Phoebe and Tryfosa show that women have long been active in ministry. However, to this day, there are still challenges for women in church mission, including restrictive theological interpretations, patriarchal culture, as well as social stigma. Therefore, the church needs to reflect on the role of women in mission by considering an inclusive theological foundation and making more room for their involvement. This study confirms that without the contribution of women, church growth and the spread of the gospel will face greater challenges.